Pengaruh Perfeksionisme dan Prokrastinasi Akademik terhadap Kemampuan Pemecahan Masalah Matematis Siswa Kelas X SMAN 1 Kediri - Wardatul Uyun; Laila Hayati; Eka Kurniawan (Mandalika Mathematics and Educations Journal, 2026)
Mathematical problem-solving ability is an essential competence in mathematics learning, contributing to the development of students’ reasoning and higher-order thinking skills, and is influenced by psychological factors such as perfectionism and academic procrastination. This study aimed to analyze the effects of perfectionism and academic procrastination, both partially and simultaneously, on the mathematical problem-solving ability of tenth-grade students at SMAN 1 Kediri in the 2025/2026 academic year. This study employed a quantitative approach with an ex post facto design. The sample consisted of 31 students selected through cluster sampling from four classes. The instruments included a perfectionism questionnaire, an academic procrastination questionnaire, and a mathematical problem-solving test based on Polya’s indicators. Data were analyzed using multiple linear regression preceded by normality, linearity, multicollinearity, and heteroscedasticity tests. The results of the prerequisite tests indicated that the data were normally distributed, the relationships among variabels were linear, and no multicollinearity or heteroscedasticity was detected. The regression analysis showed that perfectionism had a significant effect of 46.7%, while academic procrastination had a significant negative effect of 30.4%. Simultaneously, both variabels had a significant effect on students’ mathematical problem-solving ability of 59.3%..